The Information Technology Use and Skills by Undergraduate Students: Case Study - UZIAK, JACEK; LORENCOWICZ, EDMUND; KOSZEL, MILAN; KOCIRA, SŁAWOMIR (Journal of Education, Technology and Computer Science, 2018)
Information Technology (IT) is a major part of modern society and is already well embedded in everyday life. IT is believed to be a perfect tool to enhance learning, also at tertiary level. However, it is uncertain whether students use the IT for educational purposes and if that usage is at higher than basic level. The aim of the study was to investigate the use of IT by engineering students and especially their use of technology in the learning process. The study proves that the students are surrounded by common type of IT, such as smartphones and computers, and use them almost constantly. However, its use is not directed towards learning process and especially towards learning engineering applications. The knowledge and skills of programming and specialized engineering software declared by students is astonishingly low for students of engineering faculty. It appears that students’ IT ownership, access, and some, although limited, competencies have not translated into use for educational purposes.